Peran Regulasi Pemerintah dalam Kajian Minat Membayar Zakat Melalui BAZNAZ - Wisudani Rahmaningtyas; Ratieh Widhiastuti; Minhatul Maula (Sains: Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine the effect of income, knowledge of zakat, and muzakki's trust on the interest in paying zakat professionally through BAZNAZ either directly or moderated by government regulations. The study population was all Muslim civil servant teachers of SMK in Semarang City, amounting to 89 people. This research is a research with saturation side so that all members of the population become the research sample. The analysis tool uses moderated regression analysis. The results show that income, knowledge of zakat, and muzakki's trust have a significant positive effect on the interest in paying zakat on profession through BAZNAZ. Government regulations are able to strengthen the positive influence of income and knowledge of zakat, on the interest in paying professional zakat through BAZNAZ, but weaken the relationship of the positive influence of muzakki's trust on the interest in paying professional zakat through BAZNAZ.